Literature Review: Analysis of the Implementation of Responsibility Accounting in Controlling Cost in Various Organizations - Sri Trisnaningsih; Nurul Fitria (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the application of responsibility accounting in controlling costs. Responsibility accounting plays an important role in controlling company cost. The literature review approach is used to examine six pertinent papers in this investigation. The findings demonstrated that responsibility accounting plays a significant role in efficient and effective cost management via systematic reporting, budget monitoring, and excellent cost control. Various benefits are obtained from the implementation of responsibility accounting, such as overcoming the shortage of funds due to late payments, improving the smooth running of company activities, balancing the income and expenditure of the cost budget, and assisting in making better decisions and actions within the company.